Enhanced biohydrogen production from sugarcane molasses by adding Ginkgo biloba leaves. (February 2020) - Li, Weiming; Cheng, Chi; Cao, Guangli; Ren, Nanqi
Graphical abstract: Highlights: Ginkgo biloba leaves (GL) increased hydrogen production from SM by 28.03%. Cell adaptation successfully removed the inhibition of GL on cell growth. Response surface methodology was used to determine the optimized condition. Highest H2 yield of 1.58 mol/mol-hexose from SM was obtained after optimization. Metabolic flux analysis showed GL redistributed electron flux from ethanol to H2 . Abstract: Low H2 yield from biomass impedes the industrial application of biohydrogen production. To improve H2 yield, the effect of Ginkgo biloba leaf (GL) on H2 production was investigated in this study. In batch fermentation with sugarcane molasses (SM), the addition of GL improved H2 yield by 28.03%. SM medium was optimized with response surface methodology (RSM) to determine the best concentrations of GL, SM, and an inexpensive nitrogen source—corn steep liquor (CSL). A maximum yield of 1.58 mol-H2 /mol-hexose from SM was obtained when GL, CSL and SM hexose were 2.31 g/L, 2.28 g/L and 10 g/L, respectively. As observed with metabolic flux analysis, GL enhanced H2 conversion from SM via altering the metabolic flux distribution of E. harbinense from ethanol pathway towards acetate pathway. This study demonstrated the promotion effect of GL on H2 production from SM, raising a novel method for enhanced biohydrogen production in large scales.